Pengendalian Kualitas Produk Tas Di Megatama Group Menggunakan Six Sigma - Destiana Putri; Nova Pangastuti; Miwan Hidayat; Sepriandi Parningotan; Agustian Waruwu (LPPM Universitas Bina Sarana Informatika, 2022)
Business competition in the fashion industry will certainly greatly affect the level of quality that must be achieved by a company. Companies are competing to do many product innovations and improve quality and reduce reject products so that companies achieve the expected benefits or profits. If the company cannot control the quality properly, it can be imagined that the reject product will be high and this will certainly harm the company, not to mention the availability of uncertain materials can also be one of the factors hindering production. In one production of 5000 products there are 100 defective products that must be repaired. Defective products occur mostly in manual processes, namely in the gluing process. This research was conducted to find out related to quality control to reduce rejects that have been happening so far. The method used is Six Sigma DMAIC. Based on the calculation of the average DPMO value and the average sigma value of 3.7 with the possibility of damage to the production of 12,000 pcs when producing 1,000,000 pcs of bags.